2019
DOI: 10.1111/ecog.04259
|View full text |Cite
|
Sign up to set email alerts
|

Restoration potential of threatened ecosystem engineers increases with aridity: broad scale effects on soil nutrients and function

Abstract: Species extinctions alter ecosystem services, and the magnitude of this impact is likely to change across environmental gradients. In Australia, soil‐disturbing mammals that are now considered ecologically extinct are thought to be important ecosystem engineers. Previous studies have demonstrated microsite‐level impacts of reintroduced soil‐disturbing mammals on soil functions, but effects are yet to be tested across larger scales. Further, it is unclear how impacts vary across environmental gradients and if t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 85 publications
1
18
0
Order By: Relevance
“…This research suggests that biogeomorphic ecosystem engineers do not necessarily have a stronger impact in abiotically-extreme environments (also see ref. 79 ), and that the impacts of ecosystem engineers may be site-specific 26 . Indeed, it was expected that the impact of burrowing would be greater in drylands, where productivity is low 8 and resources are more limiting 51 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This research suggests that biogeomorphic ecosystem engineers do not necessarily have a stronger impact in abiotically-extreme environments (also see ref. 79 ), and that the impacts of ecosystem engineers may be site-specific 26 . Indeed, it was expected that the impact of burrowing would be greater in drylands, where productivity is low 8 and resources are more limiting 51 .…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have determined if the impacts of organisms with similar engineering roles vary across (or within) environments (although see ref. 26,79,81,82 ). As a result, there is a need to understand when ecosystem engineering is context-dependent or (relatively) context-independent, and therefore how predictable the ecological impacts of ecosystem engineering may be.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is important because the effects of digging are likely to differ between arid and temperate ecosystems (Crain & Bertness, 2006). Several studies have suggested that the effects of digging animals are more pronounced in more arid or resource-poor sites (Mallen-Cooper, Nakagawa & Eldridge, 2019; Decker, Eldridge & Gibb, 2019), however Coggan, Hayward & Gibb (2016) found the opposite pattern. Further research on ecosystem engineers in temperate ecosystems is therefore required to close this knowledge gap.…”
Section: Introductionmentioning
confidence: 99%